1984
DOI: 10.1007/bf00256849
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the kinetics of methylene-diphosphonate (MDP) and dicarboxypropan-diphosphonic acid (DPD), two radio-diagnostics for bone scintigraphy

Abstract: Two 99mTc-labelled radio-diagnostics for bone scintigraphy, dicarboxypropan-diphosphonic acid (DPD) and methylene-diphosphonate (MDP) were compared. The test parameters were the time-activity curves of serum and of deproteinised serum, time-activity curves in regions of interest above the femur, the sacrum and the soft tissue medial of the femur, and the urinary excretion. The ratio of bone lesion to normal bone was compared for 6 h after the injection of each compound. The time-activity curves in the serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…On the other hand, higher urinary excretion results in lower skeletal uptake. In humans, it was reported that the urinary excretion of MDP was 25% higher than that of DPD 21 . In an experimental study on dogs, MDP had a higher urinary excretion rate than HDP (76.5% and 59%, respectively) 18 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, higher urinary excretion results in lower skeletal uptake. In humans, it was reported that the urinary excretion of MDP was 25% higher than that of DPD 21 . In an experimental study on dogs, MDP had a higher urinary excretion rate than HDP (76.5% and 59%, respectively) 18 .…”
Section: Discussionmentioning
confidence: 92%
“…In humans, it was reported that the urinary excretion of MDP was 25% higher than that of DPD. 21 In an experimental study on dogs, MDP had a higher urinary excretion rate than HDP (76.5% and 59%, respectively). 18 Based on our review of the literature, the pharmacology of 99m Tc-diphosphonates has been poorly documented in horses.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, our study was performed on most likely sound equine limbs; therefore, HDP and MDP could not be compared regarding their lesion detection ability. Some authors reported greater retention of HDP and DPD within the skeleton; however, there was no difference between these substances and MDP in detecting bone lesions 9,29 …”
Section: Discussionmentioning
confidence: 97%
“…DPD was developed at Haechst, Germany (Schwarz and Kloss 1981;Schwarz et al 1991), and compared favorably with MDP (Buell et al 1982;Godart et al 1986;Hale et al 1981;Pauwels et al 1983;Schroth et al 1984). DPD is another efficient phosphonate complex that has been widely used as Teceos.…”
Section: Pretreatment Of Red Blood Cells (Rbc) With Mdp For In Vivo Lmentioning
confidence: 99%